Development of a CAD-Based Subprogram for Bill of Materials Generation in Midship Section Area of Cargo Oil Tank - Roisul Fadli Ahmad; Berlian Arswendo Adietya; Muhammad Luqman Hakim; Ari Santoso; Triyanda Gunawan; Hasanudin Hasanudin; Muhammad Hilmy Alfaruqi; Ardi Nugroho Yulianto (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2026)
One of the challenges in shipbuilding is managing the Bill of Materials (BOM), caused by the existence of separate BOM versions for the design, production, and maintenance stages. In addition, most BOM preparation still involves manual processes. This results in additional work in the form of BOM transformation and repeated verification, as the multiple manually created BOM versions are highly prone to data inconsistencies and duplication. This study aims to simplify BOM preparation by developing a CAD-integrated add-on program capable of automatically generating BOM from ship section design. The proposed add-on program is expected to provide a solution for facilitating BOM data transfer between shipyard divisions, thereby reducing the risk of data inconsistencies and speeding up decision-making in ship construction. The research method includes collecting material data (ship profiles and plates), creating profile and plate model templates, designing the add-on program, and developing a user guide for the add-on. The add-on program will consist of three components: Drawing Tool for modeling, Part Identification for marking structural components in the ship section design, and BOM Calculation for calculating the Bill of Materials from the structural components in the ship section design. The expected outcome of this research is the development of an add-on program capable of automatically generating a BOM from a ship’s section design, demonstrated through a case study on the cargo oil tank section in the parallel middle body of a tanker.